Terahertz shielding properties of aero-GaN [Articol] - Braniste, Tudor; Dragoman, Mircea; Alyabyeva, Liudmila; Zhukov, Sergey; Ciobanu, Vladimir; Aldrigo, Martino; Raevschi, Simion; Dragoman, Daniela; Iordanescu, Sergiu; Shree, Sindu; Gorshunov, Boris; Adelung, Rainer; et al. (IOP Publishing Ltd, 2019)
The electrodynamic properties of the first aero-material based on compound semiconductor namely of Aero-GaN, in the terahertz frequency region are experimentally investigated. Spectra of complex dielectric permittivity, refractive index, surface impedance are measured at frequencies 4–100 cm−1 and in the temperature interval 4–300 K. The shielding properties are found based on experimental data. The aero-material shows excellent shielding effectiveness in the frequency range from 0.1 to 1.3 THz, exceeding 40 dB in a huge frequency bandwidth, which is of high interest for industrial applications. These results place the aero-GaN among the best THz shielding materials known today.
Keywords: aero-GaN; complex dielectric permittivity; THz shielding